Sustainable waste-to-energy facility location: Influence of demand on energy sales. (15th September 2020) - Hrabec, Dušan; Šomplák, Radovan; Nevrlý, Vlastimír; Viktorin, Adam; Pluháček, Michal; Popela, Pavel
Abstract: Waste-to-Energy facility location with practical insights into its economic sustainability is assessed by two mathematical models. The first model minimising transportation and investment costs leads to a mixed-integer linear problem, for which commercial solvers perform very well. However, economic performance, which is needed for long-term projects requiring large investments, is not met when the capacity of the plant is not fully utilised. This can be resolved by a revenue model defining gate fees for potential plant capacities. Therefore, a second model including penalty co st functions associated with reduced energy sales and unutilised capacity of plants is developed. This leads to a non-linear model where solvers perform well for small and medium-size instances and so a modified meta-heuristic algorithm is proposed. Both models are applied to data from the Czech Republic. Insights into performance of the models and their economical sustainability using demand influence on the energy sales are provided. While the solution of the linear model proposes a higher number of facilities with less total capacity repletion, the non-linear model suggests a smaller number of facilities with higher total repletion presenting a reasonable sustainable solution. The strategy supports the decision-making of authorities for the sustainable planning of new projects. Highlights: Mathematical programming used to suggest an optimal site for Waste-to-Energy plants. Two models were developed and their results compared to evaluate sustainability. Energy utilisation included through its real sales to enhance economic performance.